Foreign Language in Nation Building: A Case Study of India - Gautam Kumar Jha (International Conference on Education and Language (ICEL), 2014)
âI do not want my house to be walled in on all sides and my windows to be stuffed. I want the cultures of all the lands to be blown about my house as freely as possible. But I refuse to be blown off my feet by any. I refuse to live in other peopleâs houses as an interloper, a beggar or a slave.Â Â  ~Mahatma GandhiâKnowledge proliferates only when thereare continuous flows of information from other sources. The continuous flow of information takes place through a medium; that is a language.Â  A language plays very important role in transmitting the knowledge from one to another.Â  There are two ways through which knowledge travels; one is through the local language and other is foreign language.Â  Local languages are similar to each other therefore knowledge does not find any challenge in passing the knowledge. However,the challenge comes when the knowledge is locked in a box of foreign language.Â  When we talk about foreign language it implies the language of the foreign land.Â  The language of the foreign land makes the knowledge lethargic to travel across the borders unless it finds its speakers beyond the borders.According to a web definition of foreign language, âa foreign language is a language indigenous to another countryâ. It is also a language not spoken in the native country of the person referred to.